(untitled) (Research, Society and Development, 2021)
Objectives: Identify how palliative care (PC) is offered for residents of brazilian favelas. Methods: This is a bibliographic review of the integrative type, from which were analyzed articles published between the year of 2014 and 2019, in the Scielo, Lilacs, Bdenf and Medline databases (via PubMed). On this study were included original articles that were available in full text and that respected the established time limit. Results and discussion: 25 articles were selected. 19 of them were about the situation of PC in Brazil and 6 of them were about PC in vulnerable communities, and they were divided in two categories: “the understanding of health access for favela’s residents” and “difficulties in accessing palliative care in poverty areas”. These articles show that the needs of people eligible for PC in favelas are unknown by public health services. Conclusion: Cultural barriers around death and dying associated with lack of financial and educational investments contribute for an incipient development of palliative care in Brazil. In addition, is important to highlight the need of further studies about the availability of this service on poor communities in Brazil to raise information to support the provision of appropriate actions to guarantee the right to health and well-being of life of this population.